Pregnancy in a Unicornuate Uterus with Non-Communicating Rudimentary Horn: Diagnostic and Therapeutic Challenges - Delić, Ratko (Acta medica Lituanica, 2020)
Unicornuate uterus with non-communicating rudimentary horn is a type of congenital uterine abnormality that occurs as a consequence of the arrested development of one of the two Müllerian ducts.Patients with unicornuate uterus have increased incidence of obstetric and gynaecological complications.We present a report of a clinical case of a 28-years-old female, who was referred to the hospital for evaluation of her infertility.The patient reported primary infertility and inability to conceive after 3-year period of regular unprotected intercourse.Transvaginal ultrasound, along with the preoperative evaluation were completed; however, no anomalies or irregularities were reported.Combined diagnostic simultaneous laparoscopy and hysteroscopy were performed to establish the diagnosis of unicornuate uterus with non-communicating rudimentary horn.The patient conceived spontaneously after diagnostic laparoscopy and hysteroscopy.During and after pregnancy, our patient and her child experienced numerous complications (cervical incompetence, acute chorioamnionitis, acute fetal distress, pneumonia, septic shock) and procedures (cervical cerclage, urgent cesarean section, intensive care unit treatment) without significant fetal or maternal compromise.
Keywords: infertility; unicornuate uterus; pregnancy; cervical incompetence; sepsis